Congenital Thoracic Wall Deformities Diagnosis, Therapy and Current Developments - Schwabegger, Anton H.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2011)
These congenital deformities, funnel or keel chest deformities, as well as Poland syndromes, affect a small group of patients who suffer from aesthetic rather than functional impairment. The wide variety of diagnoses and recommended therapies, mostly surgical procedures, can be very confusing for patients, their parents, physicians and surgeons. In recent years several techniques have been refined and developed to deal with these complex problems, and surgeons with different specialties have been operating on these deformities, mostly as lonely experts in their respective fields. This book should not be seen as an operation atlas but more as a compact survey of a small group of medical conditions and the need for flexible options for an individual therapeutic approach, based on the combined experience of different international specialists. Thus the book is designed for obstetricians, pediatricians, physicians and surgical specialists alike.
Keywords: Medicine; Surgery; Thoracic surgery; Medicine & Public Health; Surgery; Plastic Surgery; Thoracic Surgery